MENATA ULANG LEMBAGA PENDIDIKAN ISLAM SEBAGAI UPAYA MENINGKATKAN MUTU - Muhammad Fadhli (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
Islamic Education as a form of teaching and learning based on the principles and values of Islam. Education in Islam is a means towards the improvement of morals. In other words, education in Islam is a function to achieve the sublime morals, while educational institutions are aspects of material to perform these functions. Rearrangement or school improvement is a systematic effort, sustained intended to change the learning process and other related internal conditions in schools, with the goal of achieving educational goals more effectively. Structuring educational institutions as an approach to educational change that has two purposes: 1) to improve student achievement and, 2) to strengthen the school's capacity for managing change. School improvement approach everything should have the ultimate goal kepasa efforts to improve student achievement. Efforts to improve the school should not be based on the state of the schools that have a shortage / low-quality. Due to the increasingly dynamic changing times then the school must continue to improve its quality. Because the schools that already have a good quality can continue to get better again.